2023
DOI: 10.7717/peerj.14893
|View full text |Cite
|
Sign up to set email alerts
|

Association between ACE and ACTN3 genes polymorphisms and athletic performance in elite and sub-elite Chinese youth male football players

Abstract: Background Previous studies have shown controversial relationships between ACE I/D and ACTN3 R577x polymorphisms and athletic performance. Therefore, the aim of this study was to assess athletic performance indicators of Chinese youth male football players with different ACE and ACTN3 gene profiles. Methods and Materials This study recruited 73 elite (26 13-year-olds, 28 14-year-olds, and 19 15-year-olds) and 69 sub-elite (37 13-year-olds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…In the present paper, the analysis of the anthropometric variables, the ACE I/D polymorphism, and running time showed that genotype II had a correlation between running time and %F and FM pre–post running, which presented a decrease of 10.5% and 14.1% in that order. Individuals with the II genotype exhibit a higher percentage of Type I fibers and may increase bradykinin levels and decrease ACE enzyme activity so the local concentration of nitric oxide in skeletal muscle increases, thus increasing the mitochondrial respiratory efficiency and the contractile function of skeletal muscle to improve human endurance performance and fat oxidation [ 34 ]. The I allele is associated with greater fat storage during physical training.…”
Section: Discussionmentioning
confidence: 99%
“…In the present paper, the analysis of the anthropometric variables, the ACE I/D polymorphism, and running time showed that genotype II had a correlation between running time and %F and FM pre–post running, which presented a decrease of 10.5% and 14.1% in that order. Individuals with the II genotype exhibit a higher percentage of Type I fibers and may increase bradykinin levels and decrease ACE enzyme activity so the local concentration of nitric oxide in skeletal muscle increases, thus increasing the mitochondrial respiratory efficiency and the contractile function of skeletal muscle to improve human endurance performance and fat oxidation [ 34 ]. The I allele is associated with greater fat storage during physical training.…”
Section: Discussionmentioning
confidence: 99%
“…The genes ACE, ACTN3, and PPARGC1A have been among the most commonly investigated ones in this context. Even though multifactorial approaches are required, it is critical to illuminate the associations of the genes and the variations on these genes with the athletic parameters ( Cerit, 2018 ; Hall et al, 2023 ; Yang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%